Gambaran perilaku agresif pada siswa SMA di Medan Sumatera Utara - Wulantari, Masrina Naomi; Nasution, Siti Saidah; Daulay, Wardiyah (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Adolescence is a period of individual change, marked by physical and emotional or psychological changes. Emotional changes and psychological development during adolescence cause individuals to become curious about their surroundings, and vulnerable in distinguishing between good and bad. This period is often referred to as a critical period and a period of rebellion, due to emotional changes and psychological development, aggressive behavior will emerge in adolescents which can cause problems in establishing interpersonal relationships. Purpose: To identify aggressive behavior in high school students. Method: Quantitative descriptive research, conducted at Methodist High School Medan in April-May 2024. The independent variable in this study is aggressive behavior. The sampling technique used purposive sampling and the Slovin formula, the number of samples used was 26 respondents. Univariate data analysis was in the form of frequency distribution. Results: Most respondents were dominated by women as many as 16 respondents (61.5%). Most respondents were the first child as many as 11 (42.3%) and lived with their parents as many as 15 (57.7%). Most of the respondents' parents had completed secondary education, as many as 16 (61.5%) and 15 (57.7%) respectively. Most of the respondents' fathers and mothers worked as skilled workers, as many as 21 (80.8%) and 13 (50%) respectively. The respondents' aggressive behavior was included in the high category as many as 17 (65.4%). Conclusion: Adolescent girls, living with parents, first-born children, and adolescents whose parents have secondary education and whose parents work as skilled workers have high levels of aggression. Keywords: Adolescents; Aggressive Behavior; High School Students. Pendahuluan: Masa remaja adalah masa terjadinya perubahan individu, ditandai dengan adanya perubahan fisik dan emosi atau psikologis. Perubahan emosi dan perkembangan psikis dalam masa remaja menyebabkan individu menjadi ingin tahu tentang lingkungan di sekitarnya, sekaligus menjadi rentan dalam membedakan baik dan buruk suatu hal. Mas ini sering disebut pula sebagai masa kritis dan masa memberontak, akibat perubahan emosi dan perkembangan psikis, akan muncul perilaku agresif pada remaja yang dapat menyebabkan terjadinya masalah dalam menjalin hubungan interpersonal. Tujuan: Untuk mengidentifikasi perilaku agresif pada siswa SMA. Metode: Penelitian deskriptif kuantitatif, dilakukan di SMA Methodist 1 Medan pada bulan April-Mei 2024. Variabel independen dalam penelitian ini adalah perilaku agresif. Teknik pengambilan sampel menggunakan purposive sampling dan rumus slovin, jumlah sampel yang digunakan sebanyak 26 responden. Analisis data yang digunakan univariate dalam bentuk distribusi frekuensi. Hasil: Sebagian besar didominasi oleh perempuan sebanyak 16 responden (61.5%). Mayoritas responden adalah anak pertama sebanyak 11 (42.3%) tinggal bersama orangtua sebanyak 15 (57.7%). Sebagian besar orang tua responden menamatkan pendidikan tingkat menengah, masing-masing sebanyak 16 (61.5%) dan 15 (57.7%). Sebagian besar pekerjaan ayah dan ibu responden sebagai tenaga kerja terlatih, masing-masing sebanyak 21 (80.8%) dan 13 (50%). Perilaku agresif responden termasuk dalam kategori tinggi sebanyak 17 (65.4%). Simpulan: Remaja berjenis kelamin perempuan, tinggal bersama orangtua, anak pertama, dan remaja yang memiliki orangtua dengan pendidikan menengah serta orang tua yang bekerja sebagai tenaga kerja terlatih memiliki tinggi agresif yang tinggi. Kata Kunci: Emosi; Perilaku Agresif; Remaja; Siswa/i SMA.